Effect of pain on cranio-cervico-mandibular function and postural stability in people with temporomandibular joint disorders - Micoogullari, Mehmet; Yuksel, Inci; Angin, Salih (Korean Pain Soc, 2024)
Background: Neck and jaw pain is common and is associated with jaw functional limitations, postural stability, muscular endurance, and proprioception. This study aimed to investigate the effect of jaw and neck pain on craniocervico-mandibular functions and postural stability in patients with temporomandibular joint disorders (TMJDs). Methods: Fifty-two patients with TMJDs were included and assessed using Fonseca's Questionnaire and the Helkimo Clinical Dysfunction Index. An isometric strength test was performed for the TMJ depressor and cervical muscles. The TMJ position sense (TMJPS) test and cervical joint position error test (CJPET) were employed for proprioception. Total sway degree was obtained for the assessment of postural stability. Deep neck flexor endurance (DNFE) was assessed using the craniocervical flexion test. The mandibular function impairment questionnaire (MFIQ) was employed to assess mandibular function, and the craniovertebral angle (CVA) was measured for forward head posture. Results: Jaw and neck pain negatively affected CVA (R2 = 0.130), TMJPS (R2 = 0.286), DNFE (R2 = 0.355), TMJ depressor (R2 = 0.145), cervical flexor (R2 = 0.144), and extensor (R2 = 0.148) muscle strength. Jaw and neck pain also positively affected CJPET for flexion (R2 = 0.116) and extension (R2 = 0.146), as well as total sway degree (R2 = 0.128) and MFIQ (R2 = 0.230). Conclusions: Patients with painful TMJDs, could have impaired muscle strength and proprioception of the TMJ and cervical region. The jaw and neck pain could also affect postural stability, and the endurance of deep neck flexors as well as mandibular functions in TMJDs.
Keywords: Jaw; Muscle Strength; Neck; Pain; Posture; Proprioception; Temporomandibular Joint Disorders.